THE EFFECT OF PUBLIC RELATION AND CUSTOMER VALUE MARKETING ON CUSTOMER LOYALTY IN STARBUCKS COFFEE BATAM CITY - Nur Rahmah Andayani; Fedila Machbo Zania (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2021)
This research aims to determine the effect of marketing public relations and customer value on customer loyalty at Starbucks Coffee Batam City. The research variables are marketing public relation (X1), customer value (X2). The research approach uses quantitative approaches and uses descriptive statistical analysis with data processing using multiple linear regression tests with SPSS tools. The population and research sample amounted to 100 respondents. Data collection for this study uses questionnaires with a Likert Scale. The conclusion of the research are positive and significant on customer loyalty in Starbucks Coffee Batam City. Hence, maintaining customer loyalty so that customers are willing to return repeating purchases of the same product and make customers choose Starbucks Coffee products as the first choice.